Phraseological Patterns in Learner Academic English: Insights from Corpus-Driven Approaches - Sibel Aybek (Journal of the European Second Language Association)
“The language we use every day is composed of prefabricated expressions, rather than being strictly compositional” (Gray & Biber, 2015, p. 125). These prefabricated expressions contribute to the phraseology of a language, characterized by the tendency of words to occur in preferred sequences rather than occurring randomly or solely in accordance with grammatical rules (Groom, 2005; Hunston, 2002). Phraseological competence plays a pivotal role in second language acquisition (Sinclair, 1991) and mastering phraseological units specific to academic language is a crucial indicator of language development. These units help reduce processing effort for learners of academic English (Nesselhauf, 2005). This study adopts a corpus-driven approach, employing both quantitative and qualitative methods to analyze phraseological patterns and compare the linguistic productions of novice first-language (L1) and second-language (L2) and expert academic writers. Three- to four-word lexical bundles containing the most frequent grammatical keywords were extracted and classified according to their functional roles within the discourse. A qualitative contrastive analysis, guided by Granger’s (1998) principles of overuse and underuse in learner corpora, was then carried out in order to further explore the nuances of these patterns. The results suggest that using both quantitative and qualitative contrastive analysis offers valuable insights into the phraseological competence of L2 learners, particularly in academic contexts. The study examines the distribution of multi-word expressions in English L1 and L2 academic texts, contributing to the contrastive study of L2 phraseology and offering practical implications for English language teaching.